Syntheses, structural diversity and properties of a series of coordination polymers based on 4-substituted bis(triazole) and multicarboxylate ligands. (1st May 2018) - Li, Ke; Zhu, Li-Ming; Qian, Lin-Lu; Wang, Zhi-Xiang; Li, Bao-Long; Li, Hai-Yan
Graphical abstract: Seven coordination polymers based on 1, 4-bis(1, 2, 4-triazol-4-ylmethyl)benzene and multicarboxylate ligands were synthesized and characterized. Abstract: Seven coordination polymers, {[Co(btrb)(MeOip)]·H2 O} n (1 ), [Co(btrb)0.5 (NH2 ip)(H2 O)] n (2 ), [Cu(btrb)0.5 (NH2 ip)(H2 O)] n (3 ), {[Co3 (btrb)1.5 (Meip)3 (H2 O)]·3H2 O} n (4 ·3H2 O), [Zn(btrb)0.5 (1, 4-bdc)] n (5 ), [Zn2 (btrb)0.5 (Meip)2 ] n (6 ) and {[Zn2 (OH)(btrb)0.5 (btc)(H2 O)]·4H2 O} n (7 ·4H2 O) (btrb = 1, 4-bis(1, 2, 4-triazole-4-ylmethyl)benzene, H2 MeOip = 4-methoxyisophthalic acid, H2 NH2 ip = 5-aminoisophthalic acid, H2 Meip = 5-methylisophthalic acid, 1, 4-H2 bdc = terephthalic acid, H3 btc = 1, 3, 5-benzenetricarboxylic acid), were synthesized and characterized. 1 shows a 4-connected 3D cds network. 2 and 3 exhibit a (3, 4)-connected 2D network with the point symbol (4 2 ·6)(4 2 ·6 3 ·8). 4 presents a 6-connected 3D network based on a [Co3 (COO)3 ] trimeric cluster with the point symbol (4 8 ·5 4 ·6 3 ). 5 exhibits a 3-fold interpenetrated pcu network based on a [Zn2 (COO)2 ] dimer. 6 shows a 2-fold interpenetrated pcu topology based on a [Zn4 (COO)6 ] tetramer. 7 shows a rare (3, 8)-connected network based on [Zn4 (μ3 -OH)2 ] clusters with the point symbol (4·5·6)2 (4 2 ·5 6 ·6 16 ·7 2 ·8 2 ). The photocatalytic properties of 1, 3 and 4 and the solid-state photoluminescence properties of 5 –7 were investigated.